The Effect of Good Corporate Governance and Earnings Management on Audit Report Lag - Anike Putri; Muhamad Fadli Nur Insan; Elok Faiqoh Himmah; Johannes Kristian Siregar (Balance Vocation Accounting Journal, 2025)
Timely submission of financial statements is essential for companies listed on the Indonesia Stock Exchange (IDX) to maintain transparency and investor confidence. However, recent developments show an increasing number of firms delaying their financial reporting, creating urgency to examine the factors that contribute to audit report lag. This issue is particularly relevant in the consumer cyclicals sector, which is highly sensitive to economic shifts and post-pandemic recovery challenges. This study aims to analyze the influence of good corporate governance and earnings management on audit report lag. The novelty of this research lies in its focus on the 2020–2024 period, which reflects the unique conditions of the post-pandemic business environment, as well as its sector-specific analysis of consumer cyclicals companies—an area that has received limited empirical attention. This study employs a descriptive quantitative approach using secondary data obtained from the annual reports of IDX-listed firms. Multiple regression analysis is used to test the hypotheses. The results show that good corporate governance has a partially negative effect on audit report lag, indicating its role in enhancing reporting timeliness. Meanwhile, earnings management exhibits no partial effect. These findings contribute to a deeper understanding of the determinants of reporting quality within a sector undergoing dynamic economic changes.